Immature Dentate Gyrus: An Endophenotype of Neuropsychiatric Disorders - Hideo Hagihara; Keizo Takao; Noah M. Walton; Mitsuyuki Matsumoto; Tsuyoshi Miyakawa (Neural Plasticity)
Adequate maturation of neurons and their integration into the hippocampal circuit is crucial for normal cognitive function and emotional behavior, and disruption of this process could cause disturbances in mental health. Previous reports have shown that mice heterozygous for a null mutation in α-CaMKII, which encodes a key synaptic plasticity molecule, display abnormal behaviors related to schizophrenia and other psychiatric disorders. In these mutants, almost all neurons in the dentate gyrus are arrested at a pseudoimmature state at the molecular and electrophysiological levels, a phenomenon defined as “immature dentate gyrus (iDG).” To date, the iDG phenotype and shared behavioral abnormalities (including working memory deficit and hyperlocomotor activity) have been discovered in Schnurri-2 knockout, mutant SNAP-25 knock-in, and forebrain-specific calcineurin knockout mice. In addition, both chronic fluoxetine treatment and pilocarpine-induced seizures reverse the neuronal maturation, resulting in the iDG phenotype in wild-type mice. Importantly, an iDG-like phenomenon was observed in post-mortem analysis of brains from patients with schizophrenia/bipolar disorder. Based on these observations, we proposed that the iDG is a potential endophenotype shared by certain types of neuropsychiatric disorders. This review summarizes recent data describing this phenotype and discusses the data’s potential implication in elucidating the pathophysiology of neuropsychiatric disorders.